Experimental and theoretical affinity and catalysis studies between halogenated phenols and peroxidases: Understanding the bioremediation potential - Bretz, Raphael Resende; de Castro, Alexandre A; Lara Ferreira, Igor F; Ramalho, Teodorico C; Silva, Maria Cristina (Ecotoxicology and environmental safety, 2020)
Halogenated phenols, such as 2,4-dichlorophenol (2,4-DCP) and 4-bromophenol (4-BP) are pollutants generated by a various industrial sectors like chemical, dye, paper bleaching, pharmaceuticals or in an agriculture as pesticides. The use of Horseradish peroxidase (HRP) in the halogenated phenols treatment has already been mentioned, but it is not well understood how the different phenolic substrates can bind in the peroxidase active site nor how these specific interactions can influence in the bioremediation potential. In this work, different removal efficiencies were obtained for phenolic compounds investigated using HRP as catalyst (93.87 and 59.19% to 4BP and 2,4 DCP, respectively). Thus, to rationalize this result based on the interactions of phenols with active center of HRP, we combine computational and experimental methodologies. The theoretical approaches utilized include density functional theory (DFT) calculations, docking simulation and quantum mechanics/molecular mechanics (QM/MM) technique. Michaelis Menten constant (Km) obtained through experimental methodologies were 2.3 and 0.95 mM to 2,4-DCP and 4-BP, respectively, while the specificity constant (Kcat/Km) found was 1.44 mM-1 s-1 and 0.62 mM-1 s-1 for 4-BP and 2,4-DCP, respectively. The experimental parameters appointed to the highest affinity of HRP to 4-BP. According to the molecular docking calculations, both ligands have shown stabilizing intermolecular interaction energies within the HRP active site, however, the 4-BP showed more stabilizing interaction energy (-53.00 kcal mol-1) than 2,4-dichlorophenol (-49.23 kcal mol-1). Besides that, oxidative mechanism of 4-BP and 2,4-DCP was investigated by the hybrid QM/MM approach. This study showed that the lowest activation energy values for transition states investigated were obtained for 4-BP. Therefore, by theoretical approach, the compound 4-BP showed the more stabilizing interaction and activation energy values related to the interaction within the enzyme and the oxidative reaction mechanism, respectively, which corroborates with experimental parameters obtained. The combination between experimental and theoretical approaches was essential to understand how the degradation potential of the HRP enzyme depends on the interactions between substrate and the active center cavity of the enzyme.
Keywords: Biodegradation, Environmental; peroxidasy; látky znečišťující životní prostředí; Theoretical calculations; Molecular Docking Simulation; fenoly; oxidace-redukce; simulace molekulového dockingu; Peroxidases; kinetika; Catalysis; Horseradish Peroxidase; Halogenated phenols; HRP; Environmental Pollutants; Phenols; Oxidation-Reduction; křenová peroxidasa; Kinetics; katalýza; biodegradace; Experimental techniques